2015
DOI: 10.1007/s10531-015-0953-1
|View full text |Cite
|
Sign up to set email alerts
|

How much do we know about the endangered Atlantic Forest? Reviewing nearly 70 years of information on tree community surveys

Abstract: The structure of the Atlantic Forest (AF) has been studied for almost 70 years. However, the related existing knowledge is spread over hundreds of documents, many of them unpublished and/or difficult to access. Synthesis initiatives are available, but they are restricted to only a few parts or types of the AF or are focused on species occurrence. Here, we conducted an extensive review to compile quantitative tree community surveys on all types of the AF until 2013 and to study where and how these surveys were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
12

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 26 publications
0
59
0
12
Order By: Relevance
“…In addition, changes on the limits of PPAs in Scenarios III weakens the protection of the Atlantic Forest, as the considerations of Alarcon et al (2015) and Lima et al (2015) showed on permission granted by the law, which is in disagreement with Federal Law N°. 11,428/2006, as follows: "the cutting and suppression of primary vegetation or in advanced and middle stages of regeneration in the Atlantic Forest are sealed, when these are engaged in the task of protecting water sources or preventing and controlling erosion" (Brazil, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, changes on the limits of PPAs in Scenarios III weakens the protection of the Atlantic Forest, as the considerations of Alarcon et al (2015) and Lima et al (2015) showed on permission granted by the law, which is in disagreement with Federal Law N°. 11,428/2006, as follows: "the cutting and suppression of primary vegetation or in advanced and middle stages of regeneration in the Atlantic Forest are sealed, when these are engaged in the task of protecting water sources or preventing and controlling erosion" (Brazil, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The Food and Agriculture Organization of the United Nations (2014) and Lima et al (2015) stated that anthropogenic uses, as presented in the study area, are responsible for the Atlantic Forest land loss in Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…The climate is classified as Tropical with no dry season (Af) in the Köppen classification system (Alvares et al, 2013), with annual mean precipitation around 1750 mm (Saporetti-Junior et al, 2012), and mean temperature around 26 • C. Vegetation in the region is highly fragmented and predominantly composed of Atlantic rainforest remnants, Mussununga, eucalyptus plantations, pasture and crops. Mussununga is a heterogeneous savanna-type formation of different physiognomies, from grasslands, dominated by few species of monocots; savanna, composed of one layer of herbaceous plants and another layer of scattered woody plants; and woodland formed by a closed canopy (Saporetti-Junior et al, 2012;Ferreira et al, 2014;Lima et al, 2015). These vegetation patches are spread out in a matrix of Eucalyptus plantation and Brazilian Atlantic Forest (IBGE, 2004) having rounded to amoeboid shapes which greatly vary in size (less than one to hundreds of hectares).…”
Section: Study Site and Target Plant Speciesmentioning
confidence: 99%
“…Fragmentação e degradação florestal são processos que atualmente ocorrem em escala global e inevitavelmente levam, entre tantos outros, à perda de biodiversidade, mudanças climáticas locais e redução dos serviços ecossistêmicos (Magnago et al 2014, Lima et al 2015. Fragmentos florestais podem ser definidos como quaisquer áreas de vegetação nativa interrompida por barreiras antrópicas, tais como estradas e plantações ou por barreiras naturais como rios e lagos, que podem reduzir o fluxo de animais, pólen e sementes (Forman & Godron 1981).…”
Section: Introductionunclassified
“…Embora vários trabalhos sobre a estrutura do componente arbóreo da Mata Atlântica tenham sido publicados (ver Lima et al 2015), poucos levantamentos fitossociológicos foram realizados na região da Floresta Ombrófila Mista no Paraná (ver Kersten et al 2015), raramente considerando diferentes estágios sucessionais (Kozera et al 2006, Narvaes et al 2005, Piroli & Nascimento 2008. Raros também são os trabalhos que consideraram espécies lenhosas de sub-bosque desse tipo de floresta no Paraná (Barddal et al 2004, Cordeiro & Rodrigues 2007, Pimentel et al 2008, Carvalho et al 2009) nenhum considerado os estágios sucessionais.…”
Section: Introductionunclassified